1985
DOI: 10.1111/j.1432-1033.1985.tb08862.x
|View full text |Cite
|
Sign up to set email alerts
|

Two N-acetylgalactosaminyltransferase are involved in the biosynthesis of chondroitin sulfate

Abstract: 1. Two N-acetylgalactosaminyltransferases, designated I and 11, have been purified from the microsomal fraction of calf arterial tissue and separated on Bio-Gel A. 2. N-Acetylgalactosaminyltransferase I was purified 450-fold. It requires Mn2+ for maximal activity and transfers N-acetylgalactosamine residues from UDP-[l -3H]GalNAc in P-glycosidic configuration to the nonreducing terminus of the acceptor substrates GlcA(P 1 -3)Gal(P 1 -3)Gal, GlcA(P 1 -3)Gal(P 1 -4)Glc and GlcA(P 1 -3)Gal.3. Even-numbered chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 27 publications
0
27
1
2
Order By: Relevance
“…Although the relationship between the novel ␣-GalNAc T and chondroitin and/or dermatan sulfate biosynthesis is unclear, the observed modulation of the enzyme activity by the sulfated substrates implies that the enzyme might play an important role in the regulation of glycosaminoglycan biosynthesis. Rohrmann et al (21) reported that the ␤-GalNAc transferase (GalNAc T-I), which catalyzes the addition of a GalNAc to the linkage tetrasaccharide, is different from that (GalNAc T-II) which catalyzes the polymerization of a chondroitin sulfate chain. This conclusion was mainly based on the differential thermostability of the two activities, i.e.…”
Section: S 6s 6smentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relationship between the novel ␣-GalNAc T and chondroitin and/or dermatan sulfate biosynthesis is unclear, the observed modulation of the enzyme activity by the sulfated substrates implies that the enzyme might play an important role in the regulation of glycosaminoglycan biosynthesis. Rohrmann et al (21) reported that the ␤-GalNAc transferase (GalNAc T-I), which catalyzes the addition of a GalNAc to the linkage tetrasaccharide, is different from that (GalNAc T-II) which catalyzes the polymerization of a chondroitin sulfate chain. This conclusion was mainly based on the differential thermostability of the two activities, i.e.…”
Section: S 6s 6smentioning
confidence: 99%
“…Differential Thermostability of GalNAc Transferases in Serum-Previously, Rohrmann et al (21) proposed that at least two GalNAc transferase activities exist in the microsomal fraction of calf arterial tissue. One, designated GalNAc transferase I (GalNAc T-I), catalyzed transfer of the first GalNAc residue immediately adjacent to the linkage region.…”
Section: Serum Galnac Transferase Activity Toward the Commonmentioning
confidence: 99%
“…Chain polymerization for HS͞Hep is initiated once an ␣-GlcNAc is transferred to this linkage-region tetrasaccharide core by the action of ␣-GlcNAc transferase I (GlcNAcT-I) (9), whereas ␤-GalNAc transfer triggers CS͞DS synthesis (10,11). The first hexosamine transfer, therefore, is considered to be the critical determining step in which the HS͞Hep and CS͞DS chains are selected.…”
Section: H Eparan Sulfate (Hs) Is a Glycosaminoglycan (Gag) Foundmentioning
confidence: 99%
“…Then chain elongation occurs by the alternate addition of GalNAc and GlcUA residues. Enzyme activities that catalyze the initiation and elongation processes are termed glycosyltransferase-I and II activities, respectively (12). To date, six glycosyltransferases involved in CS synthesis have been identified (Fig.…”
mentioning
confidence: 99%